2020
DOI: 10.1128/mbio.02945-19
|View full text |Cite
|
Sign up to set email alerts
|

Universal Dermal Microbiome in Human Skin

Abstract: Human skin microbiota has been described as a “microbial fingerprint” due to observed differences between individuals. Current understanding of the cutaneous microbiota is based on sampling the outermost layers of the epidermis, while the microbiota in the remaining skin layers has not yet been fully characterized. Environmental conditions can vary drastically between the cutaneous compartments and give rise to unique communities. We demonstrate that the dermal microbiota is surprisingly similar among individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
82
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 55 publications
1
82
1
Order By: Relevance
“…These authors were able to identify a small bacterial community in the dermis and super cial subcutaneous adipose tissue of healthy humans. A subsequent study con rmed the existence of a bacterial community in the dermis and revealed signi cant differences in microbial composition when comparing epidermal and dermal compartments [11].…”
Section: Introductionmentioning
confidence: 91%
“…These authors were able to identify a small bacterial community in the dermis and super cial subcutaneous adipose tissue of healthy humans. A subsequent study con rmed the existence of a bacterial community in the dermis and revealed signi cant differences in microbial composition when comparing epidermal and dermal compartments [11].…”
Section: Introductionmentioning
confidence: 91%
“…As the largest organ of human body, the skin plays the primary role of physical barrier defending against the penetration of exogenous microorganisms and adverse environmental conditions [ 1 ]. Meanwhile, distinctive communities of enormous microorganisms, especially bacterial commensal inhabit on the skin, forms the diverse and complex microbial ecosystem as an epidermal microfloral community [ 2 , 3 ] and it plays an important role for the host. These symbiotic microbes-host relation actively protects the colonization of harmful or unexpected pathogens, induces immunity, and influences lipid metabolism, body odor production, and many other beneficial activity of the human host [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These symbiotic microbes-host relation actively protects the colonization of harmful or unexpected pathogens, induces immunity, and influences lipid metabolism, body odor production, and many other beneficial activity of the human host [ 4 , 5 ]. However, the microbial composition and their functions are site- and condition-specific, which are driven and shaped by the local moisture, temperature, pH, sebaceous condition, and the density of hair follicles and sweat glands [ 1 , 3 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of dermal microbiota is of doubtless physiological importance, because these microorganisms can play a role in the regulation of the delicate immune responses of the skin. Moreover, depending on their abundance and composition, the presence of a dermal or subcutaneous microbiota could also be clinically relevant [11,16]. In animals with cutaneous lesions, skin biopsies are commonly investigated with cultures and molecular techniques to detect and identify microorganisms that could have an etiologic role [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%